Performance indicators of Team Sports Performance in China - Shanshan Yang; Yangfan Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The objective of this study is to examine the role of initial workout, training and leadership in team sports performance. The moderating role of teamwork was also examined in this study. Therefore, the relationship between initial workout, training, leadership, teamwork and team sports performance was examined. To address this unique relationship, this study focused on the Chinese sports players. Data was collected from the sports players in China through quantitative research technique in which a survey was carried out. To complete a survey, this study used a questionnaire. Therefore, total 600 questionnaires were used in data collection and 250 responses were received. The analysis of the data was carried out by using a statistical software. Results of the study shows that; initial workout has positive effect on team sports performance. Training also has positive effect on team sports performance. Similarly, leadership has positive effect on team sports performance. In this direction, teamwork also play an important role to enhance the relationship between training and team sports performance. Thus, the current study has important contribution to the literature having major practical implications for the practitioners.